Patient and health care professional co-development of an Acceptance and Commitment Therapy intervention to support hormone therapy decision-making and well-being in women with breast cancer. Issue 4 (4th July 2022) - Hall, Louise Hazel; Clark, Jane; Smith, Samuel George; Graham, Christopher D.; ,
Abstract: Objectives: The aim of this work was to co-develop an Acceptance and Commitment Therapy (ACT) intervention to support medication adherence and quality of life in breast cancer survivors (BCSs). The research approach was intervention co-development. Methods: The sample consisted of BCS focus groups (n = 24), health care provider (HCP) interviews (n = 10), and a co-development workshop (BCSs, n = 12; HCPs, n = 9).We conducted 6 BCS focus groups and 10 HCP interviews to understand the acceptability of ACT. We co-designed the intervention in a workshop. Results: Participants reported high acceptability of an ACT intervention. BCSs preferred ACT exercises focused on values and self-compassion. Both groups recommended face-to-face intervention delivery, by a clinical psychologist, with a mixture of individual and group sessions. BCSs requested advice on side-effect management. Conclusions: We effectively used patient and HCP co-design to configure an ACT intervention to support medication adherence and quality of life for BCSs. If feasible and efficacious, this ACT-based intervention could support breast cancer survivorship.